2005
DOI: 10.1065/espr2005.07.273
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruption of Water and Sediment Extracts in a Non-Radioactive Dot Blot/RNAse Protection-Assay Using Isolated Hepatocytes of Rainbow Trout (14 pp).Deficiencies between bioanalytical effectiveness and chemically determined concentrations and how to explain them

Abstract: Overall, only a minor portion of the endocrine activity detected by bioassays could be linked to compounds identified by chemical analysis. In vitro assays for assessment of endocrine activities are useful as sensitive integrating methods that provide quantitative estimates of the total activity of particular receptor-mediated responses. Although discrepancies may also result from different bioanalytical approaches, it is overall likely that bioanalytical and not chemical analytical approaches give the correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 60 publications
1
30
0
2
Order By: Relevance
“…Mass-balance estimates of all major compounds contributing to the observed effects can be calculated to elucidate if all of the activity has been identified, and to assess the potential for interactions such as synergism or antagonism among contaminants present in the complex mixtures (Hilscherova et al 2000;Korner et al 2000). This strategy has been widely used for dioxin-like compounds (Safe 1990; Van den Berg et al 1998), and has recently been adopted for estrogenic chemicals (Hilscherova et al 2000;Hollert et al 2005;Khim et al 1999c;Korner et al 2000). Finally, a confirmation step in the EDA procedure evaluates how much of the observed toxicity in the environmental sample can be attributed to the mixture of identified toxicants (Brack 2003).…”
Section: The Eda Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass-balance estimates of all major compounds contributing to the observed effects can be calculated to elucidate if all of the activity has been identified, and to assess the potential for interactions such as synergism or antagonism among contaminants present in the complex mixtures (Hilscherova et al 2000;Korner et al 2000). This strategy has been widely used for dioxin-like compounds (Safe 1990; Van den Berg et al 1998), and has recently been adopted for estrogenic chemicals (Hilscherova et al 2000;Hollert et al 2005;Khim et al 1999c;Korner et al 2000). Finally, a confirmation step in the EDA procedure evaluates how much of the observed toxicity in the environmental sample can be attributed to the mixture of identified toxicants (Brack 2003).…”
Section: The Eda Processmentioning
confidence: 99%
“…By means of bioassay-directed fractionation using estrogen-sensitive systems such as MVLN or MCF7-luc cells, it could be demonstrated that the concentrations of the endogenous estrogen 17β-estradiol and the synthetic estrogen ethinylestradiol represented between 88% and 99.5% of the total estrogen equivalents in water samples from certain areas (Snyder et al 2001). However, other studies revealed that synthetic chemicals such as alkylphenolic compounds can account for the majority of the estrogenic potential of a sample (Hollert et al 2005;Khim et al 1999b;Routledge et al 1998;Sheahan et al 2002). One of the key challenges for the assessment of the contribution of individual chemicals to the bioassay derived estrogenic potential (estradiol equivalents=EEQs) of a sample is the sensitivity of the utilized analytical method, as has been demonstrated by a study assessing estrogenic compounds in complex environmental samples in the catchment area of the River Neckar, Germany (Hollert et al 2005).…”
Section: Current Eda Approaches and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kidd et al [7] demonstrated declines in populations of certain fish species after exposure to environmentally relevant concentrations of the synthetic estrogen ethinylestradiol in whole lake experiments. Additionally, various studies demonstrated the potential of sediment-bound EDCs to cause adverse effects in aquatic wildlife using different in vitro and in vivo assays [26,27,29,30,[37][38][39]. Recent studies predicted that the objective of the WFD to achieve good ecological/chemical status by 2015 is likely to fail in many European catchment areas because of the continuing remobilization of sedimentbound pollutants in heavily contaminated old sediments [40][41][42].…”
Section: Levelmentioning
confidence: 99%
“…A number of studies have been conducted to characterize the endocrine potential of municipal effluents [24,25], surface water [26][27][28] and sediments [26,27,29,30], and there has been increasing awareness of the need for testing approaches targeting EDCs to be included into current environmental assessments and monitoring [31][32][33][34][35][36] …”
Section: Environmental Sources and Exposure To Edcsmentioning
confidence: 99%